Teaching spirituality to Canadian medical students: students’ perceptions of a spiritual history taking clinical skills session - So, Tsz Ying; Kim, Kyung Young; Kornelsen, Emily; Brubaker-Zehr, Emily; Nyhof-Young, Joyce (Canadian Medical Education Journal, 2023)
Implication Statement Spirituality involves one’s sense of purpose, connection with others, and ability to find meaning in life. We implemented a three-year pilot of a spiritual history taking (SHT) clinical skills session. In small groups, medical students discussed and practiced SHT with clinical scenarios and the FICA framework and received preceptor and peer feedback. Post-session focus groups and interviews demonstrated student perceptions of improved comfort, knowledge, and awareness of discussing spirituality with patients. This innovation may support improved clinical skills teaching across other health professions institutions to better prepare students to recognize patients’ spiritual needs and provide more holistic, culturally competent care.